Compare the effect of 10 meter walk test in conventional below knee prosthesis versus modular below knee Prosthesis on unilateral transtibial Amputee patients - R. RAJA; H. RAVINDRANATH RAI; J.N. SRIDHARAMURTHY; B. MADHOURAJ; R. BALAJI; VIJAYALAKSHMI RAJA (International Journal of Pharma and Bio Sciences, 2016)
Our study is to compare the effect of 10 meter walk test on unilateral Transtibial amputees those who are using conventional and modular patellar tendon bearing (PTB) prosthesis with stump exercises. The effect of 10 meter walk test as an outcome measure to assess the time duration to walk the 10 meter distance by the unilateral transtibial amputees on the day of first PTB prosthesis fitting (1st day), at the end of 4th week and at the end of 8th week respectively and to compare the 10 meter walk test time in between conventional PTB prosthesis with stump exercises and modular PTB prosthesis with stump exercises. A sample of 120 persons with below knee amputees who were trained to wear prosthesis were studied with a comparative follow up study design with purposive sampling technique. Patients who were admitted at KIMS & RI, Bangalore, KSHMA & RI Mangalore, (N=150) who underwent unilateral transtibial, transfemoral and other amputations between Dec 2009 – Dec 2015. To find out the time duration to walk`10 meter distance by 10 meter walk test on the day of first prosthetic fitting (1st day), at the end of 4th week and at the end of 8th week (peri and post prosthetic fitting) by unilateral transtibial amputees who wear conventional and modular PTB prosthesis along with stump exercises. 6 years of comparative follow up study reveals that the outcome measures of peri and post-prosthetic fitting 10 meter walking distance time by 10 meter walk test while using conventional PTB prosthesis with stump exercises and modular PTB prosthesis with stump exercises on unilateral transtibial amputees. The unilateral transtibial amputees who trained with modular prosthesis along with stump exercises group patients 10 meter walking distance time(9.14 sec) are reduced as compared to the unilateral transtibial amputees who are trained with conventional PTB prosthesis along with stump exercises(13.84 sec). The mean difference of 10 meter walking distance time was 4.7 seconds (P<0.001). There is no significant difference seen in both the groups while giving stump exercises alone. The unilateral transtibial amputees who were trained with modular PTB prosthesis along with stump exercises group patient’s 10 meter walking distance time has reduced (P<0.001).